“Diseño de un modelo de gestión financiera para la Secretaría Nacional del Agua – Planta Central - ubicada en la ciudad de Quito - Morales Muñoz, María Fernanda (2013)
Financial Management Model for Secretaría Nacional del Agua in Central Plant located in Quito, it includes the reengineering of three Sub-processes of the Financial Direction, which are: Budget, Accounting and Treasury. Each sub-process realizes different procedures and each procedure involves a series of activities to be defined sequentially, through flowcharts that indicate in detail steps to follow within each activity. Besides, this model indicates the units or areas where the process starts up until the units or areas where it ends, and supporting documents to be submitted for each activity.